Animal Models of Metabolic Disorders in the Study of Neurodegenerative Diseases: An Overview - de Bem, Andreza Fabro; Krolow, Rachel; Farias, Hémelin Resende; de Rezende, Victória Linden; Gelain, Daniel Pens; Moreira, José Cláudio Fonseca; Duarte, João Miguel das Neves; de Oliveira, Jade (Frontiers in Neuroscience, 2021)
The incidence of metabolic disorders, as well as of neurodegenerative diseases—mainly the sporadic forms of Alzheimer’s and Parkinson’s disease—are increasing worldwide. Notably, obesity, diabetes, and hypercholesterolemia have been indicated as early risk factors for sporadic forms of Alzheimer’s and Parkinson’s disease. These conditions share a range of molecular and cellular features, including protein aggregation, oxidative stress, neuroinflammation, and BBB dysfunction, all of which contribute to neuronal death and cognitive impairment. Rodent models of obesity, diabetes and hypercholesterolemia exhibit all the hallmarks of these degenerative diseases, and represent an interesting approach to the study of the phenotypic features and pathogenic mechanisms of neurodegenerative disorders. We review the main pathological aspects of Alzheimer’s and Parkinson’s disease as summarized in rodent models of obesity, diabetes, and hypercholesterolemia.